Analysis Of Modal Words and Particles in German and Uzbek Languages - To’rayeva Fazilat Sharafiddinov (Genius Journals, 2022)
This article describes modal words and modal particles. It analyzes modal words and modal particles in German.
Keywords: Modal Word; Particles; Adverb; Syntactic Relationship